Measuring and Linking the Missing Part of Biodiversity and Ecosystem Function: The Diversity of Biotic Interactions - Pedro Luna; Erick J. Corro; Reuber Antoniazzi; Wesley Dáttilo (Diversity, 2020)
Biotic interactions are part of all ecosystem attributes and play an important role in the structure and stability of biological communities. In this study, we give a brief account of how the threads of biotic interactions are linked and how we can measure such complexity by focusing on mutualistic interactions. We start by explaining that although biotic interactions are fundamental ecological processes, they are also a component of biodiversity with a clear α, β and γ diversity structure which can be measured and used to explain how biotic interactions vary over time and space. Specifically, we explain how to estimate the α-diversity by measuring the properties of species interaction networks. We also untangle the components of the β-diversity and how it can be used to make pairwise comparisons between networks. Moreover, we move forward to explain how local ecological networks are a subset of a regional pool of species and potential interactions, γ-diversity, and how this approach allows assessing the spatial and temporal dynamics of ecological networks. Finally, we propose a new framework for studying interactions and the biodiversity−ecosystem function relationship by identifying the unique and common interactions of local networks over space, time or both together.